PENGARUH-PENGARUH TEKNIK INFORMATION GAP PADA KEMAMPUAN BERBICARA SISWA TAHUN KEDUA DI SMPN 1 SUNGAI APIT - Nurmalinda MS '; Effendy Gultom; Mahdum, Ph. D. " (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to find out whether there are significant effects of information gap technique on the speaking ability of the second year students of SMPN 1 Sungai Apit. This is a pre-experimental research conducted by using a pre-test – treatment – post-test design. This research used one group pre-test post-test design.The instrument used in this research was tests (pre-test and post-test). The population of this research was 113 of the Second Year Students of SMPN 1 Sungai Apit and the sample of this research was VIII 2 of SMPN 1 Sungai Apit which is total number of students of class was 20 students. Cluster random sampling method was used to select one class to be the sample. The data of this research were collected by giving the speaking tests (pretest-posttest) to the students. The collected data were analyzed by using t-test formula. The results of data analysis showed the mean score of pre-test was 52.47 and the mean score of post-test was 67.20.Based on the data analysis, It can be concluded that there is a significant difference between the pre-test and the post-test because the t-test observed was higher than t-table. In other words, the alternative hypothesis of this researchwas accepted and null hypothesis was rejected. It also meant that teaching speaking by using information gap technique was effective to improve the students’ speaking ability. Keywords: Speaking Ability, Information Gap, Technique